2018
DOI: 10.1038/s41598-018-21983-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the prevalence of Cognitive Impairment and its risk factors within the elderly population in Shanghai, China

Abstract: To investigate the prevalence of cognitive impairment and its risk factors among Chinese elders aged over 80 years, a community-based, cross-sectional study was conducted from May to June 2016 in Shanghai, China. Cognitive function was measured by using Mini-Mental Status Examination. Multiple logistic regression assessed associations between risk factors and cognitive impairment. Of 480 participants, 30% were diagnosed with cognitive impairment. Women [adjusted odds ratio (AOR): 1.71, 95% confidence interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
67
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 49 publications
12
67
0
3
Order By: Relevance
“…In a study carried out in Shanghai, an elderly sample (n=480) over 80 years of age for a period of 2 months using MMSE reported cognitive impairment of 30%, a finding similar to our study. 24 In the present study, psychological morbidity was 42.8% in the age range of 60-69 years. In the same age range, Tiwari and Srivastava, 1 Prasad et al 25 and Nandi et al 26 reported morbidity of 59.7%, 74% and 87.6%, respectively.…”
Section: Main Findingssupporting
confidence: 47%
See 2 more Smart Citations
“…In a study carried out in Shanghai, an elderly sample (n=480) over 80 years of age for a period of 2 months using MMSE reported cognitive impairment of 30%, a finding similar to our study. 24 In the present study, psychological morbidity was 42.8% in the age range of 60-69 years. In the same age range, Tiwari and Srivastava, 1 Prasad et al 25 and Nandi et al 26 reported morbidity of 59.7%, 74% and 87.6%, respectively.…”
Section: Main Findingssupporting
confidence: 47%
“…There is also the need to provide separate laws to deal with problems of elder abuse as had been in force for child abuse. 24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is often a lack of awareness and understanding of cognitive disorders, resulting in stigmatization and barriers to diagnosis, treatment, and management. The impact of cognitive impairment on caregivers, family, and society in general can be physical and psychological [4].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of randomized mice for in vivo cognitive-enhancing activities.All the administered drugs were prepared in normal saline (0.9% NaCl). Extract: aqueous/methanolic stem bark extracts of P. thonningii; p.o: oral administration; i.p: intraperitoneal administration 4. International Journal of Alzheimer's Disease tubes and then allowed to cool.…”
mentioning
confidence: 99%